Thrombolytic therapy in acute myocardial infarction st resolution effect in Al-kindy ccu patients - Khazaal, Faris Abdul Kareem Abdul Kareem; Kubba, Rushdi A.H.; Salman, Mohammed Abdul Jabbar; Oleiwi, Hamzah Qoneed (AL-Kindy College Medical Journal, 2014)
Background: study the effect of various risk factors on reperfusion success after thrombolysis by measuring ST resolution. Objectives: Early patency of the infarct-related artery is associated with reduced mortality. Thrombolytic therapy is frequently followed by rapid recanalization lead to reduction of infarct size, improve left ventricular function and increase survival by reopening of coronary artery . The reduction in ST-segment elevation on the standard 12 lead electrocardiogram 1-4 h after initiation of thrombolysis may be the simplest and most useful clinical tool to test the effectiveness of thrombolytic therapy. Methods: Seventy patients with acute ST elevation myocardial infarction admitted to alkindy teaching hospital CCU were studied. Early reduction of ST-segment elevation (within 1-3 hours) by >50% on the standard 12 lead ECG with single lead was measured. Results: 37(53%) of those who receive thrombolytic therapy had ST resolution within 3 hours of thrombolysis. No significant difference concerning gender with ST resolution. younger age patients respond better to thrombolysis than old significantly and with increasing number of risk factors. There is decreasing chance of early ST resolution in those with heart failure features where they had less ST resolution significantly. Serious dysrhythmia treated by DC conversion also show negative significant relation to ST resolution. Conclusions: Younger age and abscences of cardiovascular risk factors associate more early ST resolution. While late resolution may associate heart failure, serious dysrhythmia and death.